Characterization of hybrid cobalt-porous silicon systems: protective effect of the Matrix in the metal oxidation - Muñoz-Noval, Álvaro (Springer, 2012)
In the present work, the characterization of cobalt-porous silicon (Co-PSi) hybrid systems is performed by a combination of magnetic, spectroscopic, and structural techniques. The Co-PSi structures are composed by a columnar matrix of PSi with Co nanoparticles embedded inside, as determined by Transmission Electron Microscopy (TEM). The oxidation state, crystalline structure, and magnetic behavior are determined by X-Ray Absorption Spectroscopy (XAS) and Alternating Gradient Field Magnetometry (AGFM). Additionally, the Co concentration profile inside the matrix has been studied by Rutherford Backscattering Spectroscopy (RBS). It is concluded that the PSi matrix can be tailored to provide the Co nanoparticles with extra protection against oxidation.